(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
To create an opportunity to methodically form the educational trajectory, to improve the linguo-pedagogical competences of the future elementary school teachers, to have the opportunity to develop several speech skills during the completion of one educational task, to increase students’ interest in science, based on the fact that it is desirable for future elementary school teachers to have a conscious approach to the implementation of their tasks, to follow the didactic sequence in their implementation, to be able to communicate correctly with artificial intelligence in order to find tasks from modern information sources, and to introduce given.